Variation in a single allele drives divergent yield responses to elevated CO2 between rice subspecies - Yunlong Liu; Siyu Zhang; Haoyu Qian; Chengbo Shen; Shuijin Hu; Weijian Zhang; Yong Wang; Shan Huang; Songhan Wang; Zhenghui Liu; Ganghua Li; Xiangdong Fu; et al. (Nature Communications)
Abstract Rising atmospheric CO2 generally increases yield of indica rice, one of the two main Asian cultivated rice subspecies, more strongly than japonica rice, the other main subspecies. The molecular mechanisms driving this difference remain unclear, limiting the potential of future rice yield increases through breeding efforts. Here, we show that between-species variation in the DNR1 (DULL NITROGEN RESPONSE1) allele, a regulator of nitrate-use efficiency in rice plants, explains the divergent response to elevated atmospheric CO2 (eCO2) conditions. eCO2 increased rice yield by 22.8–32.3% in plants carrying or mimicking the indica DNR1 allele, but only by 3.6–11.1% in plants carrying the japonica DNR1 allele. Rice plants carrying or mimicking the indica DNR1 allele exhibit decreased eCO2-responsive transcription and protein abundance of DNR1, which activates genes involved in nitrate transport and assimilation, driving the increase in plant growth. Our findings identify the indica DNR1 gene as a key breeding resource for sustainably enhancing nitrate uptake and rice yields in japonica varieties, potentially contributing to global food security as atmospheric CO2 levels continue to increase.